Benefits or services? Politics of welfare retrenchment in Russia, 2014–2017. Issue 3 (3rd July 2021) - Matveev, Ilya
ABSTRACT: In the wake of the economic crisis of 2014–2016, the Russian government implemented tough austerity measures, earning the praise of the International Monetary Fund. However, the spending cuts were unevenly distributed across different welfare programmes, budget levels (i.e. federal and regional) as well as across different Russian regions. The article argues that this distribution is indicative of a consistent strategy of blame avoidance similar to that of the Western democracies. Specifically, the most politically sensitive budget outlays, such as pension spending, were largely protected from cuts, while areas less visible to voters, such as education, were disproportionately affected by austerity measures. Furthermore, the federal centre shifted the burden of austerity to the regions, turning regional governors into scapegoats for the federal policies. Nevertheless, in some instances fiscal considerations trumped political risk, as even cash benefits (apart from pensions) experienced deep cuts. Furthermore, the analysis of the regional spending patterns reveals that some regional governments tried to stimulate the local economy during the crisis. However, this led to even more stringent welfare austerity policies than in other regions.